Efficacy of intravascular embolization in profuse hemorrhage from complicated duodenal ulcers - D. V. Maksymchuk; V. І. Mamchich; V. D. Maksymchuk (Клінічна хірургія)
Objective. To estimate the efficacy of intravascular embolization in profuse hemorrhage from complicated duodenal ulcers.